A remarkable correlation between short period gravity waves and semiannual oscillation of the zonal wind in the equatorial mesopause region - N. Venkateswara Rao; T. Tsuda; Y. Kawatani (Annales Geophysicae, 2012)
The variability of zonal winds and the horizontal wind velocity variance of short period (20–120 min) gravity waves (GWs) in the equatorial mesopause region are studied using medium frequency (MF) radar observations from Pameungpeuk (7.4° S, 107.4° E) during 2004–2010. The zonal winds display a distinct semiannual oscillation (called mesospheric semiannual oscillation, MSAO), with westward winds during equinoxes and eastward winds during solstices. Furthermore, the westward winds during March equinox are larger during 2008 and 2009. The short period GW variance also shows a semiannual oscillation with enhanced activity during equinoxes. A good correlation is observed between the zonal winds and the short period GW variance from 2008–2010, with the winds being westward during the times of enhanced GW activity. Such a correlation, however, is less obvious during 2004–2006. The long period (10–20 h) GW variance, on the other hand, does not show such a correlation throughout the observation period.